Qualitative Research Methods - Rustamana, Agus; Adillah, Putry Maharani; Maharani, Ninda Kiyan; Fayyedh, Farell Abdiel (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Qualitative research is an approach that focuses on in-depth understanding of social phenomena and human behavior through collecting non-numerical data. This journal reviews various methods used in qualitative research, including in-depth interviews, participant observation, and document analysis. Emphasis is placed on the data collection process, thematic analysis, and validation of findings through triangulation. Apart from that, this journal also discusses the advantages and challenges faced in applying qualitative methods, such as flexibility and involvement of researchers versus subjectivity and limited generalization. By providing practical guidance and case study examples, this journal aims to assist researchers in designing and carrying out relevant and meaningful qualitative research.